URGENT PLEASE HELP
THANKS
Attachments:
![](https://hi-static.z-dn.net/files/d6a/f10674e42daf5ad1f7200c9b47d08292.jpg)
Answers
Answered by
9
Question :-
(x + 6)(x - 4)(x - 2)
Solution :-
= (x^2 - 4x + 6x - 24)(x - 2)
= (x^2 + 2x - 24)(x - 2)
= x^3 - 2x^2 + 2x^2 - 4x - 24x + 48
= x^3 - 28x + 48
Answered by
0
(x + 6)(x - 4)(x - 2)
Firstly we will simplify: (x + 6)(x - 4)
=x²-4x-6x+24
=x²-10x+24
Now,
= (x²- 10x +24)(x - 2)
= x(x²+ 10x +24)-2(x²-10x+24)
= x³- 10x²+ 24x+2x² + 20x + 48
= x³- 8x²+4x+ 48
Similar questions